2010
DOI: 10.1002/wsbm.59
|View full text |Cite
|
Sign up to set email alerts
|

Building the developmental oculome: systems biology in vertebrate eye development and disease

Abstract: The vertebrate eye is a sophisticated multi-component organ that has been actively studied for over a century, resulting in the identification of the major embryonic and molecular events involved in its complex developmental program. Data gathered so far provides sufficient information to construct a rudimentary network of the various signaling molecules, transcription factors and their targets for several key stages of this process. With the advent of genomic technologies, there has been a rapid expansion in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 185 publications
(217 reference statements)
1
48
0
Order By: Relevance
“…The ocular lens is a transparent tissue that functions to focus light on the retina, and is essential for high-resolution vision (Lachke and Maas 2010; Bassnett et al 2011). Loss of lens transparency results in an eye defect termed cataract, which is the leading cause of visual impairment worldwide (Shiels et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ocular lens is a transparent tissue that functions to focus light on the retina, and is essential for high-resolution vision (Lachke and Maas 2010; Bassnett et al 2011). Loss of lens transparency results in an eye defect termed cataract, which is the leading cause of visual impairment worldwide (Shiels et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the detailed understanding of the transcriptional circuitry that functions in early mammalian lens development and in the maintenance of anterior epithelial cells, our understanding of transcription factors that function in lens fiber cells is markedly limited (Lachke and Maas 2010; Cvekl and Ashery-Padan 2014). Besides Pax6, studies on human patients or mouse models have identified only seven other transcription factors – Prox1, Sox1, ATF4/CREB2, Pitx3, Gata3, Hsf4 and the large Maf family member, Maf (also called c-Maf) – that function to regulate gene expression in differentiating fiber cells (Donner et al 2007; Tanaka et al 1998; Kim et al 1999; Kawauchi et al 1999; Ring et al 2000; Jamieson et al 2002; Nishiguchi et al 1998; Wigle et al 1999; Bu et al 2002; Fujimoto et al 2004; Maeda et al 2009; Shaham et al 2009; Sorokina et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the crosstalk between these structures, the optic vesicle morphs into the adult retina and the lens placode gives rise to the structures of the anterior segment of eye, most notably the lens and cornea. [1][2][3][4][5] Perturbation of this precisely controlled and highly conserved developmental process can result in a wide array of clinical phenotypes, but microphthalmia (small eye) is the prototypic phenotypic consequence of arrested or impaired early development of the eye (the term "anophthalmia" is used when the eye globe fails to develop completely). 6 Microphthalmia can accompany numerous syndromes, but the majority of microphthalmia patients are nonsyndromic.…”
Section: Introductionmentioning
confidence: 99%
“…A prominent human disease associated with altered protein folding is cataract formation, with opacities caused by aggregation of lens structural proteins such as ␣-crystallins. It has been proposed that genes that are expressed in a lens-enriched manner in the developing mouse lens may have a functional role in the development and maintenance of lens transparency and, therefore, may represent candidate genes for cataract formation (32). In this approach, lens enrichment of a candidate gene is scored against its expression in whole embryonic tissues at various stages in development 3 This approach has been successful in identifying cataract loci (33).…”
Section: Absence Of Sep15 Does Not Affect Expression Of Other Selenopmentioning
confidence: 99%